Empirical observation of natural farming inputs on nitrogen uptake, soil health, and crop yield of rice-wheat cropping system in the organically managed Inceptisol of Trans Gangetic plain - Darjee, Sibananda; Singh, Renu; Dhar, Shiva; Pandey, Renu; Dwivedi, Neeta; Sahu, Pramod Kumar; Rai, Mayank Kumar; Alekhya, Gunturi; Padhan, Smruti Ranjan; Ramalingappa, Pooja Laksmidevarhalli; Shrivastava, Manoj (Frontiers in Sustainable Food Systems, 2024)
Natural Farming represents an agro-ecological methodology for farming that emphasizes regenerative practices with an aim to promote holistic ecological balance and reduce the dependence on external inputs as well as financial resources. Substantial concern has recently arisen over the need to promote agroecosystems that are more sustainable in order to improve the deteriorating soil health as well as reversing the yield plateau of crop. So, the current on farm field experiment was executed comprising of 8 treatments with different combination of natural farming inputs (Ghanjeevamrit, Jeevamrit, Beejamrit), organic fertilizer (such as FYM), integrated nutrient management (NPK, FYM, Azotobacter and Azolla) and in-organic(NPK) to examine and compare the consequence of natural farming inputs, organic fertilizer and in-organic dosage of fertilizer on soil nitrogen uptake, soil physicochemical properties, soil biological properties, soil microbial population and crop yields in a rice-wheat cropping system over two crop seasons 2021-23 [rice (Pusa-1509) and wheat ]. The study results demonstrated that there was significant (p<0.05) increase in the soil's nitrogen availability and nitrogen uptake with the use of natural farming inputs as compared to control treatment, whereas, natural farming treatments (TNF1, TNF2, TNF3, TMNF) were inferior than integrated nutrient management (TINM) and recommended doses of fertilizer (TRDF) treatment in case of nitrogen uptake by both rice and wheat crop.The outcomes demonstrated that there was significant (p<0.05) increase in the soil's nitrogen availability and nitrogen uptake with the use of natural farming inputs. Whereas non-significant changes were observed in case soil pH and electrical conductivity. The soil enzymatic activity (Dehydrogenase, β-